If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(-2-4a)-(a-6)=14
We move all terms to the left:
-4(-2-4a)-(a-6)-(14)=0
We add all the numbers together, and all the variables
-4(-4a-2)-(a-6)-14=0
We multiply parentheses
16a-(a-6)+8-14=0
We get rid of parentheses
16a-a+6+8-14=0
We add all the numbers together, and all the variables
15a=0
a=0/15
a=0
| (u-7)(u+4)=0 | | -4(2x-3)+5(-x+5)=-15 | | 7(6/x-1/5)=7 | | 2a-9=7a | | 4(a-2)+1=3a-1 | | s+44=3s-34 | | 4(-1+a)-6=-6+6a | | 4u+14=6u | | -49=-58–x/9 | | 4b+20=7b-10 | | 1.25x=135.7 | | -4k-3=-3(2k+5) | | 2z-16=z+16 | | 6*5=x(7+x) | | 10-2w=6w | | 29-x+7=2x | | 8b=-80 | | 0.1x-45=180 | | 2x+0.6=3x+0.1 | | 4.285714286=x^2+x | | x+0.1=x | | 0.3x-27=90 | | x+0.6=2x | | -3x-7=8-4x | | 9y-11=35 | | 15=x4 | | 2d+15=-d-15 | | 3x+2(4x+1)=3x+20 | | 11-11(4x-14)=649 | | -7(x+7)=48 | | 4x-22=2x+22 | | 2.1x-3.7=5.3 |